Cutting-edge technologies for business sectors - Ertugrul, Duygu Çelik; Elci, Atilla (IGI Global, 2024)
In the rapidly evolving 21st century, emerging digital technologies are transforming every aspect of modern life, from social interactions to business practices. These advancements are reshaping industries, influencing human behavior, and redefining societal structures. Understanding the impact of technologies like AI, blockchain, and virtual reality is crucial for navigating today's digital world and its challenges. Cutting-Edge Technologies for Business Sectors provides a comprehensive look at how these innovations are revolutionizing industries such as healthcare, education, law, and tourism. By exploring the ethical, practical, and societal implications of digital tools, this volume offers valuable insights for academics, professionals, and policymakers looking to harness the power of technology and shape the future. © 2025 by IGI Global. All rights reserved.